2015
DOI: 10.1186/s13071-015-0974-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic digestion of Leishmania major by host macrophages is associated with differential expression of BNIP3, CTSE, and the miRNAs miR-101c, miR-129, and miR-210

Abstract: BackgroundAutophagy participates in innate immunity by eliminating intracellular pathogens. Consequently, numerous microorganisms have developed strategies to impair the autophagic machinery in phagocytes. In the current study, interactions between Leishmania major (L. m.) and the autophagic machinery of bone marrow-derived macrophages (BMDM) were analyzed.MethodsBMDM were generated from BALB/c mice, and the cells were infected with L. m. promastigotes. Transmission electron microscopy (TEM) and electron tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
84
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 96 publications
3
84
1
5
Order By: Relevance
“…For example, induction of autophagy correlated with increased parasite loads of L. amazonensis in BALB/c, but not in C57BL/6 mice (14). A recent study using L. major infected bone marrow derived macrophages showed host autophagy was detrimental to pathogen survival (17). In contrast, it was recently reported that a stationary phase, L. major inoculum containing significant number of apoptoticlike parasites activated human macrophages autophagy machinery, thereby dampening Tcell responses and promoting parasite survival (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, induction of autophagy correlated with increased parasite loads of L. amazonensis in BALB/c, but not in C57BL/6 mice (14). A recent study using L. major infected bone marrow derived macrophages showed host autophagy was detrimental to pathogen survival (17). In contrast, it was recently reported that a stationary phase, L. major inoculum containing significant number of apoptoticlike parasites activated human macrophages autophagy machinery, thereby dampening Tcell responses and promoting parasite survival (16).…”
Section: Discussionmentioning
confidence: 99%
“…Several species of leishmania have been observed to induce host autophagy, but the molecular mechanism(s) involved in the autophagy response have only recently begun to emerge (12)(13)(14)(15)(16)(17)(18)(19). For example, two recent studies reported a link between leishmania induced autophagy and a differentially expressed set of host micro RNAs (miRNAs), including MIR-30A-3p in infected cells (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies demonstrated that L. major and L. donovani infection induce alteration of human and murine host miRNA profiles2526272829. Here, we investigate the role of L .…”
mentioning
confidence: 98%